Enhancing Employee Motivation and Ethical Work Culture through Integrated Theoretical Frameworks - Dabbagh, Firas N. (Eximia, 2024)
This research paper highlights how Integrating Equity theory, Path-Goal Leadership, and Deontological ethics shapes a balanced and ethical work environment, promoting motivation through fairness, goal clarity, and moral principles. These approaches enhance job satisfaction, commitment, and productivity by valuing employees and fostering intrinsic motivation. Creating a balanced, ethical work environment will increase job satisfaction, commitment, and productivity. The paper adopts a literature-based descriptive-analytical methodology, providing an overview of Equity Theory, Path-Goal Leadership, and Deontological Ethics and explaining how integrating these approaches influences employee motivation. The paper will extensively examine relevant literature on the three methods. Ultimately, the paper concludes that Leaders utilizing Path-Goal, Equity, and Deontological Ethics theories create motivated, goal-oriented teams, ensuring fairness, ethical decision-making, and a thriving, morally responsible workplace.